Self‐Boosting Programmable Release of Multiple Therapeutic Agents by Activatable Heterodimeric Prodrug‐Enzyme Assembly for Antitumor Therapy - Shanshan Jiang; Bhaskar Gurram; Junfei Zhu; Shan Lei; Yifan Zhang; Ting He; Oya Tagit; Hui Fang; Peng Huang; Jing Lin (Advanced Science)
Abstract Endogenous stimuli‐responsive prodrugs, due to their disease lesion specificity and reduced systemic toxicity, have been widely explored for antitumor therapy. However, reactive oxygen species (ROS) as classical endogenous stimuli in the tumor microenvironment (TME) are not enough to achieve the expected drug release. Herein, a ROS‐activatable heterodimeric prodrug‐loaded enzyme assembly is developed for self‐boosting programmable release of multiple therapeutic agents. The heterodimeric prodrug NBS‐TK‐PTX (namely NTP) is composed of 5‐(ethylamino)‐9‐diethylaminobenzo[a]phenothiazinium chloride analog (NBS), paclitaxel (PTX) and ROS‐responsive thioketal (TK) linker, which shows a strong binding affinity with glucose oxidase (GOx), thus obtaining NTP@GOx assembly. Notably, the enzymatic activity of GOx in NTP@GOx is inhibited by NTP. The programmable release is achieved by following steps: i) NTP@GOx is partially dissociated in acidic TME, thus releasing a small segment of NTP and GOx. Thereupon, the enzymatic activity of GOx is recovered; ii) GOx‐triggered pH reduction further facilitates the dissociation of NTP@GOx, thus accelerating a large amount of NTP and GOx release; iii) The TK linker of prodrug NTP is cleaved by hydrogen peroxide generated by GOx catalysis, thus expediting the release of NBS for Type‐I photodynamic therapy and PTX for chemotherapy, respectively. The NTP@GOx shows great potential for multimodal synergistic cancer therapy.